2012
DOI: 10.1007/s10433-012-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a home visitation programme for the early detection of health problems in potentially frail community-dwelling older people by general practices

Abstract: The integration within existing health care systems of preventive initiatives to maintain independent living among older people is increasingly emphasized. This article describes the development and refinement of the [G]OLD home visitation programme: an eight-step programme, including a comprehensive geriatric assessment, for the early detection of health and well-being problems among older people (C75 years) by general practices. A single group post-test study using a mixed model design is performed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Concerning the formulation of care plans, only 27.8% of the problems identified through CGA were included in a care plan, which is in agreement with our previous work [15] . It implies, as confirmed by the findings, that the formulation of care plans by PNs is not only influenced by the cut-off points of the CGA, but also by a complex interplay of patient-related and problem-specific factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning the formulation of care plans, only 27.8% of the problems identified through CGA were included in a care plan, which is in agreement with our previous work [15] . It implies, as confirmed by the findings, that the formulation of care plans by PNs is not only influenced by the cut-off points of the CGA, but also by a complex interplay of patient-related and problem-specific factors.…”
Section: Discussionsupporting
confidence: 90%
“…Also consistent with our previous work [15] , we found that the main reason for not including the remaining 72.2% of the problems in the care plan was that the problem was already known and/or action had already been undertaken. Hence, it might be argued that the ability of the [G]OLD-instrument to identify new or unmet needs that require follow-up actions is limited.…”
Section: Discussionsupporting
confidence: 90%
“…General practices (n = 21) who visited older people at home as part of our pilot study [30] were excluded from participation to prevent contamination of prior experience. We approached 188 general practices in the three regions for participation in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Applying both models has led to the development of the [G]OLD-protocol, which is explained in more detail below. Our pilot study provided preliminary evidence of the feasibility of the [G]OLD-protocol for general practices [30]. …”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence suggests frailty may be modifiable and can be prevented and sometimes even reversed [5]. Emerging frailty guidelines recommend the early identification of frailty in "at risk" seniors to address modifiable variables and prevent deterioration before it occurs [6,7]. The recognition for frailty is important especially in the primary care setting [8][9][10].…”
Section: Introductionmentioning
confidence: 99%